Anti-American terrorism from Eisenhower to Trump--a chronicle of the threat and response - Pluchinsky, Dennis A. (World Scientific, 2020)
"One of the major international security concerns that surfaced in the post-World War II period was the emergence and evolution of international terrorism. The dominant theme in the evolution of this threat has been anti-American terrorism. No other country in the world has had its overseas interests subjected to the level, lethality, diversity, and geographic scope of international terrorist activity than the United States. This four-volume work recounts the development of this threat through 12 US presidential administrations over a 70-year period. It assesses the terrorist threat in the US and overseas and how the government has responded with counter-terrorism policies, strategies, programs, organizations, legislation, international conventions, executive orders, special operations units, and actions. The evolution of the field of terrorism in academia, think tanks, institutes, and the private sector over these 12 administrations is also chronicled"--